Bivariate Distributions of Transactions: Who Borrows What? - Ravichandra Rao, I. K. (Journal of Information and Knowledge, 1981)
Based on analysis of macro-circulation data from Canadian University libraries having automated systems, it has been observed that frequent users are likely to borrow documents which are borrowed frequently and infrequent users are likely to borrow documents which are borrowed infrequently. Also, the analysis suggests that there are reasons to believe that users in the area of arts, irrespective of whether they are frequent or infrequent users, are likely to borrow documents irrespective of whether they are borrowed frequently or infrequently.